2019
DOI: 10.1111/apm.12994
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor necrosis factor treatment increases both the Th17 and Th22 T helper subsets in spondyloarthritis

Abstract: The aim was to examine anti‐tumor necrosis factor α (anti‐TNFα) therapy influence changes on Th17 and Th22 cells in patients with spondyloarthritis (SpA), and its correlation with changes in clinical and magnetic resonance imaging (MRI) activity and chronicity scores. The Th17 and Th22 cells were assessed at baseline, after 12 and 52 weeks of anti‐TNFα therapy by flow cytometry (ClinicalTrials.gov NCT4682724). The percentages of both Th17 and Th22 cells were increased by 70% at baseline compared with healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the same study, the authors found that also serum levels of IL-6, IL-17 and IL-23 significantly decreased only in responders [95]. On the contrary, an increase in IL-17+ and in IL-22+ cells after adalimumab treatment was reported by Andersen et al in 30 SpA patients [96].…”
Section: Cellular Profilingmentioning
confidence: 74%
See 1 more Smart Citation
“…In the same study, the authors found that also serum levels of IL-6, IL-17 and IL-23 significantly decreased only in responders [95]. On the contrary, an increase in IL-17+ and in IL-22+ cells after adalimumab treatment was reported by Andersen et al in 30 SpA patients [96].…”
Section: Cellular Profilingmentioning
confidence: 74%
“…An interplay of several innate and adaptive immune cell populations may be involved in SpA pathogenesis [163], and it has been reported that TNFi impact T cell populations in SpA patients [94][95][96][97]. All these observations suggest that analyzing changes in immune cells populations in SpA patients undergoing treatment may be of interest to explore disease mechanisms and therapeutic correlations.…”
Section: Cellular Profilingmentioning
confidence: 99%
“…TNF-α is a cytokine secreted by Th22 cells and Th17 cells. Andersen et al used anti-TNF-α to treat patients with spondyloarthritis (SpA) for 52 weeks of treatment ( 33 ). In this time, the number of Th22 cells and Th17 cells increased continuously, while the expression of IL-23 receptor decreased significantly.…”
Section: The Relationship Between Th22 Cells and Other Th Cellsmentioning
confidence: 99%